Over Rock and Under Stone: Carved Rocks and Subterranean Burials at Kipia, Ancash, AD 1000-1532 - Lane, Kevin John (2018)
Research in the Andes has yielded evidence for a complex association between settlement sites and mortuary monuments, tied to concepts of death, ancestor veneration and water. The Huaylas-Inca and later Spanish colonial site of Kipia in the Cordillera Negra of the Ancash Highlands, North-Central Andes is a multi-faceted site, that contains a small settlement core, and a cosmological centre which includes carved rocks (huancas), niches and offerings. This, in turn backs onto a necropolis composed of a series of subterranean tombs (pukullo). In association, these features directly reference the surrounding agro-pastoralist landscape. In particular they evoke neighbouring lakes as possible foci of ethnogenesis or pacarinas. The relation between ceremonial sites and cemeteries is crucial to understanding Andean concepts of death and renewal. In this article, alongside a detailed description of the site, we provide a preliminary analysis of the contents of one of the pukullo. In turn, these results are placed within their landscape context to discuss issues related to sacrality, water and death.